PELATIHAN PRILAKU HIDUP BERSIH DAN SEHAT BERBASIS SEKOLAH DENGAN GERAKAN KURASSAKI DI SD NEGERI 03 CIPULIR PAGI KEBAYORAN LAMA - Situmorang, Charles; Nurhayati; Siregar, Edi; Zuli, Faizal (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2023)
Elementary education caters to children aged 7 to 13, focusing on developingskills based on the curriculum, regional potential, and local socio-culturalcontexts. At SD 03 Pagi Cipulir, students are trained in various subjects, bothcurricular and extracurricular, alongside promoting a healthy lifestyle.Elementary schools are considered centers of education, with learning takingplace not only in classrooms but also outside, in activities such as teachingabout cleanliness and environmental health. Students receive training on theimportance of personal hygiene and maintaining a clean environment, aimingto instill good ethics toward their surroundings. By incorporatingenvironmental education early on, it is expected that students will carry thesevalues into the future. This approach is intended to positively impact thestudents of SD 03 Pagi Cipulir, South Kebayoran Lama, and to raiseawareness of environmental cleanliness within the broader community,fostering a sustainable, healthier, and environmentally-conscious future for allgenerations now.